Water Quality Parameters: A Case Study of Karnafully River Chittagong, Bangladesh - Sarwar, M Iqbal; Majumder, Ahmad Kamruzzaman; Islam, M Nurul (Bangladesh Journal of Scientific and Industrial Research, 2010)
The river Karnafully is one of the Himalayan River originating from the Lushai Hills in India. The catchments of the Karnafully and its allied streams cover 5,500 (14,000 sq km) square miles. Water samples were collected from Karnafully River along different points and analyzed for various physiochemical parameters during winter. Effects of industrial wastes, municipality sewage and agricultural runoff on the river water were investigated. The study was conducted between the Kaloorghat Bridge and Patenga estuary including Chittagong port. This is the most polluted area due to the presence of many chemical fertilizers, iron, leather and pharmaceutical industries. All these industries discharge their untreated toxic waste water directly into the river Karnafully. The study involved determination of physical and chemical parameters of surface water at different points. The mean values of water temperature, total suspended solids (TSS), total dissolved solids (TDS), total solids (TS), turbidity, dissolved oxygen (DO), bio-chemical oxygen demand (BOD), chemical oxygen demand (COD), pH, electric conductivity and total alkalinity were 23°C, 365.87 mg/L, 8018.8, 8518.33 mg/L, 31.54 FTU, 1.55 mg/L, 6.65 mg/L, 13961 μs/cm, 247.47 mg/L, 560.27 mg/L and 4.8 mg/L respectively. Key words: Physiochemical parameters; Winter season; Monsoon season; Dissolved oxygen; Biological oxygen demand. DOI: 10.3329/bjsir.v45i2.5722 Bangladesh J. Sci. Ind. Res. 45(2), 177-181, 2010